INDIVIDUAL PREFERENCES: A REASON TO USE CODE SWITCHING TO TEACH ENGLISH - Agustinus Semiun (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2011)
Abstract It is usual for non-native EFL teachers to use code switching and or code mixing as a medium of instruction due to a number of factors such as inadequate oral ability of the teachers, complexity level of teaching topics, curriculum and poor basic English of the students. However it is unusual if the teachers of great oral ability maximize if not always use code switching for most of the time during instruction. The present article tries to explain the code switching and or code mixing performed by the EFL teachers in senior high schools spreading over the West Timor land, the province of Nusa Tenggara Timur and the factor of “individual preferences” as their reason why teachers of great oral ability favor to use code switching and or code mixing during classroom instruction like those of lower or inadequate oral ability of English. The data recorded and presented in this article prove that the teachers use code switching in four types that might be similar or different from those in other places in Indonesia. Abstrak: Sudah sangat biasa guru-guru bahasa Inggris yang bukan “native speakers” menggunakan alih kode (code switching) dan atau cmpur kode (code mixing) sebagai medium pembelajaran bahasa Inggris karena berbagai factor, di antaranya kemampuan oral guru, tingkat kompleksitas materi ajar, pemahaman terhadap kurikulum, dan rendahnya pengetahuan dasar bahasa Inggris siswa. Namun sangat tidak lasim kalau guru-guru yang berkemampuan oralnya di atas rata-rata kalau tidak sempurna, selalu menggunakan alih kode atau campur kode selama proses pembelajaran di kelas. Artikel ini mencoba mengulas alih kode dan atau campur kode sebagai medium mengajarkan bahasa Inggris para guru SMA sedaratan Timor Barat propinsi Nusa Tenggara Timur serta factor “individual preference” sebagai dasar keputusan untuk menggunakan alih kode dan atau campur kode tersebut. Berdasarkan data dapat diidentifikasi serta diklasifikasi ke dalam empat jenis alih kode dan atau camput kode yang bukan tidak mungking berdbeada dari guru-guru lain di luar NTT.